Neuroblastoma - Shimada, Hiroyuki (IntechOpen, 2013)
Tumors of neuroblastoma group are heterogenous and their molecular/genomic properties are closely related to the prognosis of patients: some children enjoy an excellent clinical course after biopsy/surgery alone, and others suffer from a fatal outcome even after an intensive treatment. Recent progress has also started disclosing critical significance of cross-talking between neuroblastoma cells and their microenvironment in predicting clinical behaviors of individual cases. In this book, the world distinguished investigators report clinical and biological characteristics of this disease.